Effects of Accounting Information Systems on Financial Performance of Micro, Small and Medium Enterprises in Kenya - Ochieng, Omolo Kennedy; Nyamita , Micah Odhiambo; Lucas, Stephen Okelo (EuroEconomica, 2025)
Accounting information systems have been viewed as a game changer in helping MSMEs to avert crises by availing accurate, timely, and sufficient financial information for decision-making. Despite Accounting Information Systems facilitating accountability and transparency to MSMEs, businesses in Homa Bay Town are still facing the challenge of poor record keeping. This study therefore assessed the effects of accounting information systems on the financial performance of Micro- Small and Medium Enterprises in Homa Bay Town, Kenya using primary data collected from 161 MSMESs. The study applied Record Keeping Systems, Financial Reporting Systems, Cash Management Systems and Enterprise Resource Planning Systems as the main measures of accounting information systems. Descriptive and inferential statistics such as multiple regression techniques were used to analyze the data. The regression results showed that record keeping systems had the strongest influence (Beta = 0.329, p = 0.000), followed by Cash Management Systems (Beta = 0.263, p = 0.000), Financial Reporting Systems (Beta = 0.154, p = 0.034), and Enterprise Resource Planning Systems (Beta = 0.165, p = 0.015). Based on the findings, it was recommended that organizations prioritize the improvement of accounting information systems majorly record-keeping systems and cash management systems.